PERSPEKTIF AL-QUR’AN TENTANG NUSYŪZ, ILĀ’ DAN ẒIHĀR - Mahfiani, Rifka (Institut Agama Islam Negeri Bone, 2024)
ABSTRACTThis research discusses the Qur'anic perspective on nusyÅ«z, ilÄ' and áº“ihÄr. This study aims to find out the nature of nusyÅ«z, ilÄ' and áº“ihÄr in the Qur'an, the form of nusyÅ«z, ilÄ' and áº“ihÄr in the Qur'an, and their implications in the household. This research is a library research that is included in the qualitative descriptive type. The research data sources consist of primary data and secondary data analyzed through a thematic approach. The results show that etymologically, nusyÅ«z comes from Arabic taken from the word nasyaza, yansyuzu, nusyuzan which means high or rising to the surface, while in terms it is defined as a husband or wife who leaves the obligations of husband and wife which brings estrangement between them in their status as husband and wife who are legal according to applicable law.Â NusyÅ«z that occurs in the household will result in divorce. IlÄ' comes from the Arabic word ÄlÄ - yuwÄli - ilÄ' which means oath, while in terms it is defined as a husband's oath not to have sexual intercourse with his wife. In the Qur'an, the word ilÄ' is repeated 37 times in the Qur'an. If the husband still does not want to have intercourse with his wife without an excuse, the qadhi can again decide that his wife has been given a second divorce and the husband still has the right to reconcile. Furthermore, áº“ihÄr according to Arabic comes from the word Ø¸Ù‡Ø§Ø± which means back. Whereas in terms is the speech of a mukallaf to his wife that she is the same as his mother. In the Qur'an, the word áº“ihÄr is mentioned 57 times with various redactions, áº“ihÄr will also result in husband and wife no longer being obliged to live together and create a basis for the division of joint property as if the marriage was dissolved.Â ABSTRAKPenelitian ini membahas mengenai perspektif al-Qurâ€™an tentang nusyÅ«z, ilÄâ€™ dan áº“ihÄr. Penelitian ini bertujuan untuk mengetahui hakikat nusyÅ«z, ilÄâ€™ dan áº“ihÄr dalam al-Qurâ€™an, wujud nusyÅ«z, ilÄâ€™ dan áº“ihÄr dalam al-Qurâ€™an, serta implikasinya dalam rumah tangga. Penelitian ini merupakan penelitian kepustakaan (library research) yang termasuk dalam jenis deskriptif kualitatif. Sumber data penelitian terdiri dari data primer dan data sekunder yang dianalisis melalui pendekatan tematik. Hasil penelitian menunjukkan bahwa Secara etimologis, nusyÅ«z berasal dari bahasa Arab yang diambil dari kata nasyaza, yansyuzu, nusyuzan yang berarti tinggi atau timbul ke permukaan, sementara secara istilah diartikan sebagai suami atau istri yang meninggalkan kewajiban bersuami istri yang membawa kerenggangan hubungan di antara keduanya dalam status sebagai suami istri yang sah menurut hukum yang berlaku.Â Dalam al-Qurâ€™an,> nusyÅ«z disebutkan sebanyak lima kali dalam al-Qurâ€™an. NusyÅ«z yang terjadi dalam rumah tangga akan berakibat pada perceraian. IlÄâ€™ berasal dari bahasa Arab yaitu ÄlÄ â€“ yuwÄli - ilÄâ€™ yang berarti sumpah, sedangkan secara istilah diartikan sebagai sumpah suami untuk tidak menggauli istrinya. Dalam al-Qurâ€™an, kata ilÄâ€™ terulang sebanyak 37 kali dalam al-Qurâ€™an, apabila suami tetap tidak mau mencampuri istrinya tanpa uzur, maka qadhi Â dapat kembali memutuskan bahwa istrinya telah dijatuhi talak kedua dan suami masih berhak rujuk. Selanjutnya áº“ihÄr menurut bahasa Arab berasal dari kata Â Ø¸Ù‡Ø§Ø±yang bermakna punggung. Sedangkan secara istilah adalah ucapan seorang mukallaf kepada istrinya bahwa dia sama dengan ibunya. Dalam al-Qurâ€™an, kata áº“ihÄr disebutkan sebanyak 57 kali dengan redaksi yang beragam, áº“ihÄr juga akan mengakibatkan suami istri tidak lagi diwajibkan tinggal bersama dan menimbulkan dasar untuk pembagian harta bersama seakan-akan perkawinan itu dibubarkan.